South Korea the enigmatic peninsula - Dake, Mark A. (Dundurn, 2016)
"Mark Anton Dake, a Canadian ESL teacher, set out on a four-month road trip to discover everything that South Korea had to offer. From art galleries and temples to mountaintops and national parks, The Enigmatic Peninsula shares the heart and soul of Koreans and their beautiful country."--